2016
DOI: 10.1111/jch.12882
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Organ Damage in White‐Coat Hypertension: The Possible Role of Cystatin C

Abstract: The authors investigated the relationship of white-coat hypertension (WCH) with subclinical organ damage and potential relevant mechanisms. A total of 386 untreated patients were enrolled and divided into 204 patients with WCH and 183 with normotension. Flow-mediated dilation (FMD), pulse wave velocity (PWV), intima-media thickness, left ventricular mass index (LVMI), and cystatin C levels were measured. All tests were two-sided, and a P value <.05 was considered statistically significant. The WCH group exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In the study where non‐dipping was first defined, patients with a non‐dipping BP profile had a significantly higher stroke risk . The results of some subsequent studies support a link between non‐dipping status (elevated nocturnal BP) and a higher rate of cardiovascular events, but others failed to find such an association …”
Section: Resultsmentioning
confidence: 99%
“…In the study where non‐dipping was first defined, patients with a non‐dipping BP profile had a significantly higher stroke risk . The results of some subsequent studies support a link between non‐dipping status (elevated nocturnal BP) and a higher rate of cardiovascular events, but others failed to find such an association …”
Section: Resultsmentioning
confidence: 99%
“… 7,8,16‐20 Most of the studies were conducted in Greece, whereas the other studies were conducted in Brazil, France, and Italy, being published between 2004 and 2019. Only three studies provided arterial stiffness details for all the hypertension phenotypes, 7,8 1 study compared only WCH with normotensives, 16 while one study compared WCH with both normotensives and sustained hypertensives 18 . The other two studies compared c‐f PWV in the MH and normotensive group and/or hypertensive group 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, CysC has been long-regarded as a stable serum biomarker that reflects glomerular filtration function (7). Furthermore, it has been reported that elevated serum CysC is also related to the risk of hypertension (8,9), hypertension-induced myocardial hypertrophy (10)(11)(12), chronic and acute heart failure (13,14), hypertensive nephropathy (15,16), and cardiovascular disease morbidity and mortality (17)(18)(19)(20)(21)(22). Some researchers have found that excluding the influence of renal function, increased serum CysC levels still have diagnostic and prognostic value (17,18).…”
Section: Introductionmentioning
confidence: 99%